A Design of SDN Based IP Mobility Management Considering Inter-Domain Handovers and Its Evaluation - Misumi Hata; Mustafa Soylu; Satoru Izumi; Toru Abe; Takuo Suganuma (Advances in Science, Technology and Engineering Systems Journal, 2017)
To use IP services continually while users are moving with their mobile devices, IP mobility management that enables them to keep IP communication is necessary. Although Mobile IP is a popular method to manage IP mobility, Mobile IP has a problem that there is a possibility of a mobile node (MN) communicating over a redundant route. Then, Software Defined Network (SDN) based IP mobility management has emerged to solve this problem. Most of these solutions focus on intra-domain handovers and routing. However, since wireless network environment has spread, mobile devices move across domains during communication. To deal with this, we need to look upon inter-domain handovers and routing. In this paper, we propose a SDN based IP mobility management scheme considering situation of mobile devices moving across domains. This proposed scheme focuses on inter-domain handovers and introduces efficient functions of management information sharing and inter-domain routing. Experimental results show the desired effects of the proposed scheme: optimizing communication route and keeping the management information exchange traffic low.
Keywords: IP mobility; Mobility management; Software Defined Network; Inter-domain